Allan Brooks, Naturalist and Artist (1869-1946): The Travails of an Early Twentieth Century Wildlife Illustrator in North America - Winearls, Joan (Scientia Canadensis, 2008)
AbstractBritish by birth Allan Cyril Brooks (1869-1946) emigrated to Canada in the 1880s, and became one of the most important North American bird illustrators during the first half of the twentieth century. Brooks was one of the leading ornithologists and wildlife collectors of the time; he corresponded extensively with other ornithologists and supplied specimens to many major North American museums. From the 1890s on he hoped to support himself by painting birds and mammals, but this was not possible in Canada at that time and he was forced to turn to American sources for illustration commissions. His work can be compared with that of his contemporary, the leading American bird painter Louis Agassiz Fuertes (1874–1927), and there are striking similarities and differences in their careers. This paper discusses the work of a talented, self-taught wildlife artist working in a North American milieu, his difficulties and successes in a newly developing field, and his quest for Canadian recognition.